Jurisprudential Controversies of Establishing Sperm Bank - mohammad hossein rahmati; Narjes Nazari Nouleh (فقه و حقوق خانواده)
Today, sperm is stored in special banks in order to donate it to infertile couples or to use it for the owner of the sperm, when incidents occur that reduce his fertility. The establishment and activity of these banks in Islamic countries have been the subject of jurisprudential debates by some scholars, including whether it is correct to trade sperm, considering its impurity and lack of wealth and receiving large sums of money for handing it over to these banks? Does not donating foreign sperm to infertile couples violate the right to identity and destroy the lineage of children born from these sperms? Is storing sperm and injecting it into a stranger's womb or injecting it into the wife's womb after the death of the sperm owner compatible with the ruling principles and rules in Shia jurisprudence? This research, which is done by descriptive- analytical method, has been analyzed these controversies and concluded that first, despite the local and rational benefits of sperm donation, there is no obstacle in its trade, just as donating it to infertile couples does not cause the loss of the lineage of the children born from these methods and does not violate their right to identity. Secondly, injecting sperm into a stranger's womb or the wife's womb after the death of the owner of the sperm does not have any obligation and none of the aforementioned disputes is an obstacle to establishing a sperm bank and using it from a jurisprudential point of view.